Unveiling Cybercrime Trends in India: Leveraging Residual Neural Networks and Novel Deep Learning Techniques for Dataset Analysis - Busane Aditya, J. Eswar, Dr. Jyothi N. M., Nidamanuri Vishnu, Pawan Jha (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The aim of this study is to investigate and analyze cybercrime trends in India using advanced deep learning techniques, particularly focusing on the application of residual neural networks (ResNets) and novel methodologies for dataset analysis. By unveiling and understanding the evolving landscape of cyber threats and criminal activities, this research seeks to provide insights into the prevalence, patterns, and characteristics of cybercrimes in the Indian context. The study utilizes a comprehensive dataset comprising reported cybercrime incidents in India, sourced from official law enforcement agencies and cybercrime databases. Preprocessing techniques, including data cleaning, normalization, and feature engineering, are applied to prepare the dataset for analysis. Residual neural networks (ResNets), known for their ability to handle complex data structures and capture hierarchical features, are employed for modeling cybercrime patterns. Novel deep learning techniques, such as attention mechanisms and ensemble learning, are integrated to enhance model performance and interpretability. The dataset is divided into training, validation, and test sets, and the ResNet-based models are trained using supervised learning techniques. The application of Residual Neural Networks (ResNets) and novel deep learning techniques yields promising results in uncovering cybercrime trends in India. The trained models demonstrate high accuracy in classifying and predicting various types of cybercrimes, including phishing attacks, malware infections, financial frauds, and identity thefts. Analysis of model outputs reveals insights into the temporal and geographical distribution of cybercrimes, as well as emerging trends and modus operandi adopted by cybercriminals. Moreover, visualization techniques and interpretability tools are employed to elucidate the underlying factors driving cybercrime incidents in different regions of India. In conclusion, this study highlights the efficacy of leveraging Residual Neural Networks (ResNets) and novel deep learning techniques for analyzing cybercrime trends in India. By harnessing the power of advanced machine learning algorithms and comprehensive datasets, this research contributes to a deeper understanding of the cyber threat landscape and provides valuable insights for law enforcement agencies, policymakers, and cybersecurity professionals. The findings underscore the importance of proactive measures and collaborative efforts in combating cybercrimes, safeguarding digital assets, and protecting the interests of individuals and organizations in an increasingly interconnected world.